2011
DOI: 10.1086/657686
|View full text |Cite
|
Sign up to set email alerts
|

How an Organism Dies Affects the Fitness of Its Neighbors

Abstract: Programmed cell death (PCD), a genetically regulated cell suicide program, is ubiquitous in the living world. In contrast to multicellular organisms, in which cells cooperate for the good of the organism, in unicells the cell is the organism and PCD presents a fundamental evolutionary problem. Why should an organism actively kill itself as opposed to dying in a nonprogrammed way? Proposed arguments vary from PCD in unicells being maladaptive to the assumption that it is an extreme form of altruism. To test whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 25 publications
2
65
0
2
Order By: Relevance
“…Growth dynamics were atypical due to the relatively nutrient-depleted media (PCD supernatant obtained after 1-2 days). The effect of PCD on growth of the same species was positive ( figure 2a,b), consistent with previous reports [5,11]. Unexpectedly, PCD supernatant from C. reinhardtii CC125 inhibited the growth of two other species, C. moewusii ( figure 2c,d) and C. debaryana (figure 2e,f ).…”
Section: Results and Discussion (A) Induction And Detection Of Prograsupporting
confidence: 91%
See 1 more Smart Citation
“…Growth dynamics were atypical due to the relatively nutrient-depleted media (PCD supernatant obtained after 1-2 days). The effect of PCD on growth of the same species was positive ( figure 2a,b), consistent with previous reports [5,11]. Unexpectedly, PCD supernatant from C. reinhardtii CC125 inhibited the growth of two other species, C. moewusii ( figure 2c,d) and C. debaryana (figure 2e,f ).…”
Section: Results and Discussion (A) Induction And Detection Of Prograsupporting
confidence: 91%
“…The mechanism is unknown; however, in another chlorophyte, Dunaliella salina, PCD releases organic materials that are either used directly by D. salina cells not undergoing PCD or re-mineralized by a co-habiting archaeon [11]. A similar mechanism may be at work in Chlamydomonas and is supported by our previous findings that the active ingredients are simple heat-stable molecules [5].…”
Section: Results and Discussion (A) Induction And Detection Of Programentioning
confidence: 73%
“…Alternatively, white-to-opaque switching during stationary phase-a period typically characterized by nutrient limitation and increasing concentrations of farnesol-could result in a unique altruistic cooperation within the culture where the subpopulation that switches to opaque is killed by farnesol (8), resulting in the release of nutrients into the surrounding medium. Unicellular algal species, such as Chlamydomonas reinhardtii, release beneficial nutrients into the surrounding medium during programmed cell death (37), but this type of altruistic behavior has yet to be seen in a Candida species. A mechanism for triggering cell death within a subset of the Candida community, for example, within the matrix of a biofilm, could improve survival within a host.…”
Section: Figmentioning
confidence: 99%
“…Although protozoan apoptosis has been argued to be an altruistic trait [9,108], evidence of benefit to surviving con-specifics is, so far, scarce. Durand and colleagues [109] have shown that the contents of the unicellular green algae, Chlamydomonas reinhardtii , were beneficial to colony members if PCD occurred, but harmful if it was non-PCD. However Segovia et al [110] claim that members of a colony of the chlorophyte Dunaliella tertiolecta that were kept in the dark did not gain from death associated with DNA fragmentation, caspase-like activity and morphological features of apoptosis of some members.…”
Section: Reviewmentioning
confidence: 99%